Sosialisasi Modul “Hukum Islam dan Lingkungan” untuk Meningkatkan Pemahaman Menjaga Lingkungan Hidup dan Keberlanjutan Alam - Ikhwan, M.; Muhammad Ghazali; Fitri Hidayati; Rika Hasmayanti Agustina; Gusti (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This community service activity on the dissemination of an Islamic law module plays a significant role in fostering students' awareness and responsibility toward environmental preservation. Through the socialization of the Islamic Law and Environment module, students at the Madrasah demonstrated a notable improvement in their understanding of Islamic principles related to environmental sustainability. Evaluation results indicate that students not only comprehended the concepts of Islamic law concerning the environment but also actively participated in environmental initiatives, such as campaigns and tree planting, reflecting the practical application of these values in daily life. The module has effectively equipped students with the necessary knowledge to implement Islamic teachings in preserving nature and has encouraged them to become environmentally conscious agents of change. The application of Islamic legal principles in education and social practices can strengthen environmental sustainability at both local and global levels. By integrating Islamic values into education, a younger generation can be nurtured with a greater sense of responsibility toward nature, capable of applying religious teachings to maintain harmony between humanity and the environment.